Activation patterns of covert word generation detected by fMRI: comparison with 3D PET - Sadato, N; Yonekura, Y; Yamada, H; Nakamura, S; Waki, A; Ishii, Y (Journal of computer assisted tomography, 1998)
The aim of our study was to compare the activation patterns of higher cognitive function detected by functional MRI (fMRI) with those by H2(15)O positron emission tomography (PET). Activation studies with both modalities were performed in six normal volunteers with identical covert word generation tasks and statistical analysis. For PET, each subject had five rest scans and five task scans at 10 min intervals. fMRI was performed with a 1.5 T magnet using T2*-weighted echo planar sequences. Each scanning session consisted of two rest and two task periods of 30 s each, alternating rest and task. In group analysis, the activation patterns on both PET and fMRI were similar, whereas the deactivation patterns differed, presumably due to the noise of fMRI. In single-subject analysis, PET showed fewer activated areas and fMRI showed more areas of activation than in group analysis. fMRI has an advantage over 3D PET in its better signal-to-noise ratio for detecting change in neuronal activity for higher brain function.